2007
DOI: 10.1677/erc-06-0050
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin upregulates sphingosine kinase-1 expression and activity in the human breast cancer cell line MCF7 and triggers enhanced proliferation and migration

Abstract: Sphingosine kinases (SK) catalyze the formation of sphingosine-1-phosphate (S1P) which plays a crucial role in cell growth and survival. Here, we show that prolactin (PRL) biphasically activates the SK-1, but not the SK-2 subtype, in the breast adenocarcinoma cell-line MCF7. A first peak occurs after minutes of stimulation and is followed by a second delayed activation after hours of stimulation. A similar biphasic effect on SK-1 activity is seen for 17b-estradiol (E 2 ). The delayed activation of SK-1 derives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 40 publications
0
44
0
Order By: Relevance
“…Hypothetically, it might work within a similar scheme shown for phytoestrogen signalling in MCF-7 cells. Supporting this both, GPR30 and ERa were involved in oestrogen-dependent activation of SphK1 (Sukocheva et al 2003, Doll et al 2007). The exact mechanisms underlying rapid (15-30 min) SphK1 activation by E 2 also remain elusive, leaving the possibility of direct or adaptormediated interactions between ERa, GPR30 and SphK1 still unexplored.…”
Section: Figurementioning
confidence: 68%
See 2 more Smart Citations
“…Hypothetically, it might work within a similar scheme shown for phytoestrogen signalling in MCF-7 cells. Supporting this both, GPR30 and ERa were involved in oestrogen-dependent activation of SphK1 (Sukocheva et al 2003, Doll et al 2007). The exact mechanisms underlying rapid (15-30 min) SphK1 activation by E 2 also remain elusive, leaving the possibility of direct or adaptormediated interactions between ERa, GPR30 and SphK1 still unexplored.…”
Section: Figurementioning
confidence: 68%
“…There is strong evidence demonstrating that SphK1 has an important growth-regulatory role in BCC (Doll et al 2007, Rosen & Goetzl 2005, Sukocheva et al 2006. Other authors (Doll et al 2007) and we (Sukocheva et al 2003) have demonstrated that in BCC the proliferation-stimulating steroid hormone oestrogen activates the SphK1 (Fig.…”
Section: Figurementioning
confidence: 73%
See 1 more Smart Citation
“…Prolactin plays a functional role in tumor cell proliferation and promotes survival of breast, prostate, endometrial, and other cancer cells [68][69][70][71]. Several epidemiological studies have shown a consistent relationship between prolactin levels and known risk factors for breast cancer such as parity and age at menarche [68].…”
Section: Other Stress Mediatorsmentioning
confidence: 99%
“…Similar to E2, prolactin biphasically activates SK1 with acute activation of SK1 and late phase activation via SK1 gene transcription (Fig. 2) (Doll et al 2007). Lastly, progesterone has been shown to regulate SK1.…”
Section: Hormonesmentioning
confidence: 94%